Hotel tsunami preparedness in the coastal tourism destination - Wulung, Shandra Rama Panji; Abdullah, Cep Ubad (Journal of Business on Hospitality and Tourism, 2022)
This study aims to identify the condition of hotel industry post-tsunami and its preparedness in Anyer, Carita, and Tanjung Lesung area. This research was conducted for six months from April to September 2020. The method employed was a qualitative. The primary data of this study were acquired through observation, in-depth interviews, and questionnaires. The secondary data were collected through previous studies and the regional government policies. The data were analyzed in a qualitative analysis. This study showed that the hotels have not been applying tsunami-ready hotel before the disaster occurred. The absence of tsunami standard operational procedure is one of the biggest causes to the big number of casualties